DINAMIKA PENERAPAN GREEN ECONOMY DALAM PENGEMBANGAN LOKASI PARIWISATA UPAYA MEWUJUDKAN PEMBANGUNAN BERWAWASAN LINGKUNGAN DALAM TINJAUAN EKONOMI ISLAM - Iriawan, Olivia Anggraini; Saefurrohman, Ghina Ulfah; Devi, Yulistia; A.Aisyah, A.Aisyah; Nurhayati, Nurhayati (LAN TABUR : Jurnal Ekonomi Syariah, 2024)
This research has observations regarding the application of green economy in managing the location of tourism objects in the Sumber Agung area, namely the Lengkung Langit 2 tourist attraction. Where its application will affect environmental conditions, the level of tourist visits, tourist comfort, and the economy of the affected communities. Assessing the ability to implement a green economy in producing shipping industrial areas with the ultimate goal of supporting environmentally friendly changes, Uncovering the elements that can occur when implementing a green economy in the development of shipping industrial areas with the ultimate goal of promoting environmentally friendly changes. Explain the relationship between the idea of implementing a green economy and the idea of sharia financial issues based on the Koran and Hadith. The research method used in conducting this research is a qualitative method with a phenomenological approach. The research results show that the Lengkung Langit 2 tourism location has implemented several green economy principles in managing tourist attractions which influence the success in realizing environmentally conscious development with supporting and inhibiting factors therein. From an Islamic economic perspective, its implementation is in accordance with the development orientation in Islam. Keywords: Green Economy, Environmentally Responsive Development, Islamic Economic